A Review of the Knowledge Base for the Communication Skills of Educa-tional Administrators - Gomez, Abigail C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Few studies dwell on the communication skills of educational administrators. Most of the research results yielded from credible international indexing sites focus more on educational management style, supervision, and administration; thus, the difficulty to survey a bigger scope for this field of interest. Still, this study examined various studies which concentrate on interpersonal skills or communication skills of educational administrators, leaders, and principals. Twenty research articles selected around the globe completed from 2010 to 2021 were utilized in this review. Quantitative analysis of the research findings provided evidence of the relevance of these skills to becoming effective educational administrators. The selected articles reveal that this field of interest is more prevalent in the Philippines and Nigeria. Most researchers utilized the descriptive survey method. Various questionnaires were used, but the instruments Principal's Communication Style Questionnaire and the organizational climate description were most frequently used. Finally, this review reveals that common research structure revolves around the correlation between the educational administrators’ communication skills and styles and the organization and teachers.